Upaya pencegahan penyakit diare dengan metode enam langkah cuci tangan yang benar pada santri Pondok Pesantren Thawalib Sriwijaya Palembang - Tia Sabrina; Tyas Hestiningsih; Rima Zanaria (Fakultas Kedokteran Universitas Sriwijaya, 2020)
The incidence of diarrhea is still high in Indonesia. This disease mostly affects children, especially school-age children. One of the easy and simple preventive steps is apply proper handwashing. The purpose of this study is to increase the knowledge of students of the Islamic Boarding School Thawalib Sriwijaya Palembang about the six-step method of washing hands. The participants are 55 students from 7th-grade junior high school to 12th-grade high school. The method consist of lectures, discussions and direct practice of how to wash hands properly. Evaluation is carried out using a pre-test and post-test questionnaire. The result of the paired T-test obtained p=0.000 with a mean difference of pre-test and post test is -4,000 and 95% confidence intervals is -4,429 to - 3,571. There was an increase in participants' knowledge about how to prevent diarrheal diseases by applying the six-step method of washing hands properly.